2001
DOI: 10.1002/1522-2683()22:6<1175::aid-elps1175>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of phosphorus-containing amino acid-herbicides by nonionic surfactant micellar electrokinetic chromatography with laser-induced fluorescence detection

Abstract: The potential of micellar electrokinetic chromatography (MEKC) with laser-induced fluorescence (LIF) detection for the separation and determination of phosphorus-containing amino acid-herbicides (glufosinate and glyphosate), and aminomethylphosphonic acid (the major metabolite of glyphosate), involving derivatization with fluorescein isothiocyanate (FITC) isomer I, was investigated. Different variables that affect derivatization (pH, FITC concentration, time and temperature) and separation (pH and concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 37 publications
1
20
0
1
Order By: Relevance
“…So, for natively fluorescent or labelled analytes absorbing in the UV region, He-Cd laser (325 nm) and frequency-doubled Ar ion laser (257 nm) have been widely employed [7][8][9][10][11][12][13][14][15], using built in-house equipment or coupling laser sources with commercial CE systems. For labelled fluorescent analytes with absorption in the visible region, FITC is the most widely used derivatizating reagent due to its compatibility with commercial air cooled argon ion laser (488 nm) LIF detector [16][17][18][19][20][21]. For labelled fluorescent analytes with absorption in the visible region, FITC is the most widely used derivatizating reagent due to its compatibility with commercial air cooled argon ion laser (488 nm) LIF detector [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…So, for natively fluorescent or labelled analytes absorbing in the UV region, He-Cd laser (325 nm) and frequency-doubled Ar ion laser (257 nm) have been widely employed [7][8][9][10][11][12][13][14][15], using built in-house equipment or coupling laser sources with commercial CE systems. For labelled fluorescent analytes with absorption in the visible region, FITC is the most widely used derivatizating reagent due to its compatibility with commercial air cooled argon ion laser (488 nm) LIF detector [16][17][18][19][20][21]. For labelled fluorescent analytes with absorption in the visible region, FITC is the most widely used derivatizating reagent due to its compatibility with commercial air cooled argon ion laser (488 nm) LIF detector [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Brij-35 was added to the MRB, because it has been recently reported that nonionic surfactants can significantly improve the separation of closely related anionic analytes without affecting the ionic current during the run and thus avoiding excessive Joule heating [13]. (iii) The use of neutral micelles allowed to achieve a good separation for the amino compound derivatives; however, this pseudostationary phase shows an important inhibitory effect on the labeling reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Among the most frequent excitation sources, the argon ion laser emitting at 488 nm is employed for exciting a wide range of fluorescent derivatives, which are formed by reaction of the analytes with suitable reagents. FITC [9][10][11][12][13] is very popular due to the high-quantum yield of its moiety. Recently, 5-(4,6-dichloro-s-triazin-2-ylamino)fluorescein (DTAF) has been receiving attention as an alternative to FITC due to its faster labeling reaction, higher purity and lower cost [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used chromatographic separation methods include high-performance liquid chromatography (HPLC) [9,10], gas chromatography (GC) [11], liquid chromatography-tandem mass spectrometry (LC/MS) [12], gas chromatography-tandem mass spectrometry (GC-MS/MS) [13,14], capillary electrophoresis (CE) [15-18], and enzyme-linked immunosorbent assay (ELISA) [2,3,19]. For example, an analytical method has been reported for quantifying dl -glufosinate enantiomers in biological specimens using precolumn derivatization and reversed-phase HPLC with a fluorescence detector.…”
Section: Introductionmentioning
confidence: 99%